Start-up of simultaneous nitrification, anammox and denitrification-sequential batch reactor (SNAD-SBR) for treating anaerobic palm oil mill (POME) Digester Effluent - Wong, W.-S. (Institute of Physics Publishing, 2020)
Simultaneous Nitrification, Anammox, and Denitrification (SNAD) which was discovered around 2008 has become a promising alternative to conventional nitrogen treatment process. The increasing number of researches on SNAD can be seen lately from lab-scale experiment to full-scale operation around the world. However, due to complexity of mutual relationship between three different bacteria, more researches are needed to be done to have better understanding of SNAD on real-scale application. This study is aimed to examine the performance of SNAD on treating effluent from anaerobic digester of palm oil mill effluent. The study will discuss cultivation of anammox, completion of SNAD process, and the feasibility of SNAD on effluent from anaerobic digester. The result of this study will help in explore further application of SNAD besides treating nitrogen-rich wastewater. Â© Published under licence by IOP Publishing Ltd.